FAKTOR PENYEBAB PERCERAIAN DAN PERAN BINTAL DALAM MENEKAN KASUS PERCERAIAN KELUARGA PRAJURIT/PNS DALAM MENDUKUNG KETAHANAN KELUARGA (STUDI KASUS PERCERAIAN DI BINTALDAM JAYA) - , Suyadi; , Prof. Drs. Kasto, MA, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Every couple who lived in a household has always longed for a happy family, spiritual and physical welfare. But all of spouse can make it happen, not even the otherwise harmonious family and ended in divorce, although they were aware that the actual divorce is lawful / unlawful but hated by Allah SWT. Before the 1998 reform of divorce in families of soldiers and civil servants is a taboo subject, because it is disgrace to the family and will affect the personâs career and rank. But after the reform era as the development of information disclosure and divorce in families of soldiers and civil servants to be increased. This study wanted to see what is the factor causing the divorce and how the mental coaching role in suppressing the rate of divorce and how the mental coaching role in supporting family resilience (done in Bintaldam Jaya). the result show that there are 10 causes of divorce for families of soldiers and civil servants Military District and six of the eight functions of the family who can not function properly and therefore contributes to divorce as well as the factors are not influential in information disclosure and divorce of the career and service, mental coaching has a role positive in harmony and happiness of the household but have not been able to push the divorce rate, divorce is merely delaying the time course, whereas in the mental development of family support has a positive role. Therefore, an effort that needs to be achieved by bintal is to multiply the time for guidance, counseling and care to the families of soldiers and their families civil servants to be harmonized to support family resilience.